Behavior and Ecological Study of Marine Birds in Alas Purwo National Park Southern Cost - Indonesia - Sholihah, Raudatus (KnE Life Sciences, 2017)
Alas Purwo National Park is habitat for marine birds and stopover for some the migratory birds. The purpose of this research was to determine behavior that could be observed in populations of marine birds and their habitat in the Alas Purwo National Park. The research location was in the Alas Purwo National Park southern coast, in region Plengkung to Cungur, Banyuwangi East Java. This research was done for 2 mo, July 21 to 30 and August 2015. The observations were observed in the morning (at 6:00 am to 9:00 am) and afternoon (15:00 pm to 18:00 pm). This study used a purposive sampling method to determine the location of the observations near the coast. The observations of marine birds habitat and behavior used survey methods and direct observation at the plot along the coastline. Identification and calculation of marine bird populations conducted in each observation plots. The plots exploration by foot and repeated three times. The behavior of marine birds that can be observed were birds clustered beach sunbathing on the beach, wallowing in the water, drinking and foraging in the surrounding water and flew low over the waters up to the mangrove areas for perch. Marine birds habitat are in mangrove and near the coast with moderate temperatures, high air humidity, low water temperature, and light intensity is sufficient. Keywords: Alas Purwo national park; behavior; ecological study; habitat; marine bird.